2023
DOI: 10.1097/psy.0000000000001215
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience to Trauma and Risk of COVID-19 Infection and Somatic Symptoms Across 2 Years

Abstract: Objective Exposure to trauma increases the risk of somatic symptoms, as well as acute and chronic physical diseases. However, many individuals display psychological resilience, showing positive psychological adaptation despite trauma exposure. Resilience to prior trauma may be a protective factor for physical health during subsequent stressors, including the COVID-19 pandemic. Methods Using data from 528 US adults in a longitudinal cohort study, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Studying on somatic symptoms and resilience, Nishimi,Tan, Scoglio, Choi, Kelley, Neylan, O'Donovan (2023) found that lower levels of somatic symptoms associated with higher resilience during the pandemic, adjusting for COVID-19 infection and long COVID status [29]. Resilience found to reduce the adverse effects of stressors on immunity and immune processes also influence resilience [30].…”
Section: The Concept Of Resiliencementioning
confidence: 99%
“…Studying on somatic symptoms and resilience, Nishimi,Tan, Scoglio, Choi, Kelley, Neylan, O'Donovan (2023) found that lower levels of somatic symptoms associated with higher resilience during the pandemic, adjusting for COVID-19 infection and long COVID status [29]. Resilience found to reduce the adverse effects of stressors on immunity and immune processes also influence resilience [30].…”
Section: The Concept Of Resiliencementioning
confidence: 99%